Professional Values and Job Satisfaction Levels of Pediatric Nurses and Influencing Factors: A Crosssectional Study - Ayla Kaya; Derya Çelik; Ayşegül İşler Dalgıç (Galenos Yayinevi, 2020)
Aim:The aim of this cross-sectional study was to investigate the perceptions of professional values and job satisfaction levels of pediatric nurses and their influencing factors.Materials and Methods:This study was conducted with 134 nurses working in the pediatric clinics of three hospitals in Turkey. Nurses' Professional Values scale and Minnesota Job Satisfaction Questionnaire were used to collect the data.Results:It was found that the pediatric nurses had high professional values and that job satisfaction scores were moderate. It was further noted that pediatric nurses who were single, received their education in a nursing high school, had professional experience of 11-15 years in pediatric clinics, were working as clinical responsible nurse, and were working during the day shift regularly had higher scores of professional values. It was found that the job satisfaction of the pediatric nurses who were married, received their education in a nursing high school, had professional experience of 11-15 years in pediatric clinics, were working as clinical responsible nurse, and were working at day shift regularly, was significantly higher than the others. The results also indicated a positive and high correlation between pediatric nurses' perception of professional values and job satisfaction levelsConclusion:It was concluded that promoting professional values among nurses would eventually result in increasing levels of job satisfaction. We believe this study provides substantial data in this particular field in Turkey and it is hoped that it may be used to guide nursing managers to design well-established and unbiased programs for pediatric nurses.